Vaccines for Piscirickettsiosis (Salmonid Rickettsial Septicaemia, Srs): The Chile Perspective - Maisey-Munoz, K; Montero, R (Taylor and Francis Ltd, 2017)
Introduction: Piscirickettsia salmonis (P. salmonis) is the aetiological bacterium of the contagious disease piscirickettsiosis or salmonid rickettsial septicaemia (SRS) and causes significant economic losses to aquaculture production in Chile. Current strategies to control infection are i) indiscriminate antibiotic use and ii) vaccination with predominantly P. salmonis bacterin vaccines that do not provide acceptable levels of protection against piscirickettsiosis. Areas covered: This review covers the basic biology of P. salmonis, clinical piscirickettsiosis and disease control, the development of current P. salmonis vaccines, innate and adaptive immunity and a 5-year plan to develop new piscirickettsiosis vaccines. Expert commentary: Fundamental knowledge is lacking on the complexities of P. salmonis-host interactions, relating to bacterial virulence and host innate and adaptive immune responses, which needs to be addressed. The development of new P. salmonis vaccines needs the application of comprehensive ‘omics’ technologies to identify candidate vaccine antigens capable of stimulating long-lasting protective immune responses. © 2016 Informa UK Limited, trading as Taylor & Francis Group.